2003
DOI: 10.1002/anie.200351810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatial Dimensions of Fully Aromatic Dendrimers

Abstract: Do dendrimers in solution have a dense shell or a dense core? This question can be answered with the help of small‐angle neutron scattering. The fully aromatic dendrimer G4‐M shown here displays the expected rigid structure in solution and represents the first example of a real dense‐shell dendrimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…[250,251] Neutron diffraction experiments have shown that they are denser at the periphery than at the core. [252] As a result of this rigidity any two groups within the dendrimer or upon its surface are in well-defined spatial relationships to each other, which is of great importance for controlling their electronic interactions, particularly the transfer of excitation energy between them. It also means that the shape of the empty space between groups in the interior of the dendrimer is well-defined and, as a consequence of the limited mobility of the benzene rings within the structure, relatively invariant, which offers the possibility of manipulating this space by synthetic design so as to produce great selectivity for guest molecules.…”
Section: Dendrimers As Vessels For Chemistry Physics and Biologymentioning
confidence: 99%
“…[250,251] Neutron diffraction experiments have shown that they are denser at the periphery than at the core. [252] As a result of this rigidity any two groups within the dendrimer or upon its surface are in well-defined spatial relationships to each other, which is of great importance for controlling their electronic interactions, particularly the transfer of excitation energy between them. It also means that the shape of the empty space between groups in the interior of the dendrimer is well-defined and, as a consequence of the limited mobility of the benzene rings within the structure, relatively invariant, which offers the possibility of manipulating this space by synthetic design so as to produce great selectivity for guest molecules.…”
Section: Dendrimers As Vessels For Chemistry Physics and Biologymentioning
confidence: 99%
“…[21][22][23][24] In general, dendrimers bearing rigid -conjugating backbones are known to have a dense shell and a sparse core. 25,26 The nano-space around the core unit is utilized as a molecular-capsule for capturing metal ions, [27][28][29][30][31][32][33] clusters, [34][35][36][37][38][39][40][41][42] or other guest molecules. 43,44 The dendrimers can manage electron [45][46][47] or energy [48][49][50][51][52][53][54][55][56][57][58] transfer between the core and the periphery due to their unique density-gradated architecture.…”
Section: Metallo-dendrimer Complexesmentioning
confidence: 99%
“…A design strategy for such an unusual system is to utilize the unique dense shell property of rigid dendrimers. 25,26 All dendrimers reported as ligands for multi-metal ion assemblies have flexible backbones composed of single covalent () bonds. However, they are not suitable for precise metal assembly because their conformational changes and back-folding with thermal vibrations would prevent the precise discrimination of the coordination sites.…”
Section: Fine-controlled Metal Assembling In Dpas (Dendritic Phenylazmentioning
confidence: 99%
“…[3] In Konsequenz wird die räumliche Form der PPDs durch die Geometrie ihres Kerns vorgegeben, sodass allein durch die Verwendung von unterschiedlichen Kernmotiven (Abbildung 1 a-c) vielfältige Dendrimerstrukturen erhalten werden können. [4] Zur Synthese möglichst kugelförmiger Strukturen konnten bislang nur vierarmige Tetraederkerne (Tetraphenylmethan, Abbildung 1 c) eingesetzt werden, [5] da höhere Symmetrien, wie beispielsweise die eines Oktaeders, mit den Mitteln der organischen Synthesechemie nur schwer zu generieren sind.…”
Section: Professor Klaus Hafner Zum 80 Geburtstag Gewidmetunclassified
“…Demgegenüber ermöglicht die metallorganische Chemie die Herstellung von Koordinationsverbindungen mit höheren Symmetrien. Ein Beispiel ist der bekannte Tris(2,2'-bipyridyl)ruthenium(II)-Komplex ([Ru(bpy) 3 ], Abbildung 1 d), [6] der sich bereits als Kern für nicht formstabile Dendrimere bewährt hat. [7][8][9] Ziel dieser Studien war es meist, den Einfluss dendritischer Hüllen auf die Eigenschaften des Ruthenium-Chromophors zu untersuchen [8] oder molekulare Lichtsammelsysteme zu generieren.…”
Section: Professor Klaus Hafner Zum 80 Geburtstag Gewidmetunclassified